2021
DOI: 10.3390/toxins13100702
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Uremic Clearance Granules in Uremic Pruritus: A Meta-Analysis

Abstract: Uremic pruritus is common among patients with advanced or end-stage renal disease, with an incidence of >40% among patients on dialysis. Uremic clearance granules (UCGs) are effective in managing uremic pruritus and delay the progression of chronic kidney disease. We conducted a systematic review and a meta-analysis to evaluate the efficacy of UCG in patients with uremic pruritus. Several electronic databases were searched systematically from their inceptions until 19 July 2021. Randomized control trials ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…In addition, the long-term nature of uremic treatment and the burden of treatment costs will also aggravate patients' loss of confidence in treatment [37,38]. Therefore, the key to psychological care for patients with uremia is to let patients accept it slowly from unwilling to accept it, change their negative cognition of their life, and let patients understand that uremia can live like healthy people through treatment, so as to stimulate patients' confidence in active treatment and good life [39][40][41]. The method adopted in this study is a new branch of cognitive behavioral therapy, that is, reception-based therapy, which is aimed at helping the treatment object accept and actively deal with their own psychological problems [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the long-term nature of uremic treatment and the burden of treatment costs will also aggravate patients' loss of confidence in treatment [37,38]. Therefore, the key to psychological care for patients with uremia is to let patients accept it slowly from unwilling to accept it, change their negative cognition of their life, and let patients understand that uremia can live like healthy people through treatment, so as to stimulate patients' confidence in active treatment and good life [39][40][41]. The method adopted in this study is a new branch of cognitive behavioral therapy, that is, reception-based therapy, which is aimed at helping the treatment object accept and actively deal with their own psychological problems [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Although several hypotheses have been suggested for the pathogenesises of CKDaP, chronic inflammation has been recently recognized as one of the major pathogenic factors [20][21][22][23][24][25]. Kimmel et al reported that higher levels of serum CRP, IL-6, and TNF-α were found in hemodialysis patients with CKDaP compared with those without CKDaP [21].…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire covered the criteria of the itching sensation, including duration, degree, direction, distribution, and disability, such as spleen disruption and social dysfunction. Severity of pruritus scoring was defined as non-present (≤8), mild (9)(10)(11), moderate (12)(13)(14)(15)(16)(17), severe (18)(19)(20)(21), and extreme (≥22). Patients answered the same questionnaire at baseline and post-supplementation.…”
Section: Pruritus Questionnairementioning
confidence: 99%
“…Accumulation of P, Ca, Al, and Mg can contribute to pruritus [ 37 , 38 , 39 ]. Hypercalcemia and hyperphosphatemia were identified as independent risk factors for CKD-associated pruritus [ 9 ].…”
Section: Pathogenesis Of Ckd-associated Pruritusmentioning
confidence: 99%